The Influence of Realistic Mathematics Approach on Mathematical Problem Solving Ability of Students of SMP 4 Medan - Intan Udana Siahaan (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to determine the improvement of students' mathematical problem-solving abilities through the implementation of the Problem Based Learning (PBL) model in junior high school students. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The participants consisted of 30 eighth-grade students selected through purposive sampling. The research instrument was a mathematical problem-solving ability test consisting of five essay questions validated by experts. Data were analyzed using normality tests, paired sample t-tests, and N-Gain analysis. The results showed that the average pretest score was 58.47 and increased to 83.13 in the posttest. The paired sample t-test indicated a significance value of 0.000 < 0.05, showing a significant difference between pretest and posttest scores. Furthermore, the average N-Gain score was 0.60, categorized as moderate. These findings indicate that the Problem Based Learning model effectively improves students' mathematical problem-solving abilities. Therefore, PBL can be used as an alternative instructional model to foster higher-order thinking skills in mathematics learning.